1988
DOI: 10.1021/bi00418a019
|View full text |Cite
|
Sign up to set email alerts
|

Anion binding to neutral and positively-charged lipid membranes

Abstract: Aqueous anion binding to bilayer membranes consisting of 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC) was investigated by using deuterium and phosphorus-31 nuclear magnetic resonance (NMR) spectroscopy. Only those anions that exhibit chaotropic properties showed significant binding to POPC membranes. A detailed investigation of thiocyanate binding to neutral POPC and to positively charged mixed POPC/dihexadecyldimethylammonium bromide (DHDMAB) (8:2 mol/mol) membranes revealed changes in the 2H NMR q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(79 citation statements)
references
References 32 publications
6
73
0
Order By: Relevance
“…Numerous examples for unspecific interactions of chaotropic anions with biological membranes are also known;7, 162, 168, 169, 170, 171, 172, 173, 174 in particular, their membrane‐disrupting properties are noteworthy 171, 172. Gabel and co‐workers investigated the interaction between dodecaborate cluster dianions and lipid bilayers;34, 35, 36, 175 at high salt concentrations they observed changes in the morphology of liposomes as well as bilayer leakage (see Figure 8 for an example).…”
Section: Examplesmentioning
confidence: 99%
“…Numerous examples for unspecific interactions of chaotropic anions with biological membranes are also known;7, 162, 168, 169, 170, 171, 172, 173, 174 in particular, their membrane‐disrupting properties are noteworthy 171, 172. Gabel and co‐workers investigated the interaction between dodecaborate cluster dianions and lipid bilayers;34, 35, 36, 175 at high salt concentrations they observed changes in the morphology of liposomes as well as bilayer leakage (see Figure 8 for an example).…”
Section: Examplesmentioning
confidence: 99%
“…Instead, ions can interact with the bilayer and modify its structural, interfacial, and electrostatic properties. Experiments have shown that anionic 4, [22][23][24][25] and cationic 26,27 membranes interact readily with their counterions (especially divalent ones), whereas the interactions of zwitterionic lipid bilayers with salt ions appear rather sensitive to the size and valency of ions. [28][29][30][31][32][33][34][35][36][37][38][39][40][41] As for molecular-level computational studies, the increase in computing power in the past few years has made it possible to extend computer simulations beyond the relatively long relaxation times of tens to hundreds of nanoseconds required for equilibration of ions in lipid/water systems.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, in phosphate solutions, many PO 3 − anions gather on the outer parts of the film. It has been shown that charged anions affect the absolute value of the CSA by decreasing it (shifting the σ ⊥ peak to the left) [20,21]. We propose that charges remaining from the preparation of the AAO substrate interact with the lipid bilayer and cause a slight shift in the 31 P NMR spectrum of AAO substrate bound lipids, not an increase in motional dynamics.…”
Section: Resultsmentioning
confidence: 75%